Improvement of the material and technical base of agriculture in Kazakhstan - Batyrova, N.; Mombekova, G.; Yerzhanova, S.; Yessimzhanova, S.; Turkmen, F. (BUKETOV BUSINESS REVIEW, 2018)
Nowadays, the mechanization of production process has led to economic crises especially in the agricultural sector. These crises bring to the agenda that states can not provide effective financial support to the whole agricultural sector. For this reason, in order to ensure economic stability of the states and later support for all sectors, it will be appropriate to develop agricultural complexes in a sustainable manner, especially in the rural areas by developing appropriate site and production techniques. Because the inability to keep pace with the development of the market economy and the inadequate implementation of the reforms constitute the first phase of the systematic crisis in the production of local agricultural products. In this study, problems related to commercial structures and technical support problems in Kazakhstan's agriculture sector, direct investments in production of agricultural products and fixed assets, almost all depreciation charges and profit margin were handled as literature review. Within the scope of the study it was determined that the technical data continued to fall and those who live in rural areas should be provided with support to purchase new equipment and new production factors in order to solve technical support problems.